2010
DOI: 10.1093/aje/kwq125
|View full text |Cite
|
Sign up to set email alerts
|

Teens and Screens: The Influence of Screen Time on Adiposity in Adolescents

Abstract: The effect of screen time during secondary school on percent body fat was examined in a cohort of 744 Canadian adolescents aged 12-13 years at baseline. Participants completed self-reported questionnaires on television viewing and computer use in 19 survey cycles over 57 months from 1999 to 2005. Triceps skinfold thickness and subscapular skinfold thickness were measured in survey cycles 1 and 19. Four screen-time trajectory groups identified in growth mixture modeling included steady-low screen time (73% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 53 publications
4
31
0
3
Order By: Relevance
“…These games encourage the participants to remain sedentary for longer periods of time relative to the other activities. This finding resembled earlier research where increased screen time reduced discretionary time for physical activity [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These games encourage the participants to remain sedentary for longer periods of time relative to the other activities. This finding resembled earlier research where increased screen time reduced discretionary time for physical activity [12].…”
Section: Discussionsupporting
confidence: 89%
“…As a consequence, it might be expected that greater time on the computer and particularly the Internet might be associated with greater body mass index (BMI). Increased screen time among high school teens supported the displacement hypothesis [11] whereby in this case increased screen time reduces discretionary time for physical activity in one study [12]. Electronic games might involve more movement or physical activity, in certain cases depending on the game console (e.g., Wii) and type of game played (e.g., sports).…”
Section: Introductionmentioning
confidence: 55%
“…However, in three of the studies reporting an association, the analyses were not adjusted for the outcome measure at baseline [21,23,27] . In addition, in one of the studies, this association was found in boys but not in girls [26]. Similar findings were reported in another study, where computer time predicted increases in skinfold thickness in both boys and girls and increased BMI in boys, whereas time spent TV viewing predicted changes in BMI and hip circumference in boys, but not in girls [25].…”
Section: Young Peoplesupporting
confidence: 83%
“…In adults, physical activity together with other covariates attenuated the association between sedentary behavior and weight gain in all studies but one [32]. In children and adolescents, adjusting for physical activity attenuated the association in one study [22], and moderated the association in one study [26]. Some of the observed associations may be explained by residual confounding due to poorly measured or unmeasured confounders or bias due to misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation